Annual world Bank Conference on development Economics 1995 : [proceedings] - World Bank Annual Conference on Development Economics Washingon, D.C. 1995; Bruno, Michael; Pleskovic, Boris (Washington,D.C World Bank, 1995)
The 1995 conference addresses four themes: (1) where we stand on inequality, poverty, and growth; (2) demographic change and development; (3) aid and development; and (4) fiscal decentralization. The first theme centers around a book by Hollis Chenery, Redistribution With Growth, which discusses: (a) the constant elasticity of substitution production functions to economies of scale; (b) the complementarity and timing of investment decisions; (c) investment criteria and shadow pricing; (d) dynamic comparative advantages; and (e) issues of income distribution and growth. This book has made two important contributions to development economics: it has established the intellectual base for research and policy analysis at the Bank, and has changed the course of thinking on development, especially on how to help the poor. The second theme refers to government provision and regulation of economic support in old age, and new perspectives on women, work, and demographic change. The theme of aid and development focuses on incentives and guidelines for development, reasons behind multilateral lending, and whether or not growth in developing countries is beneficial to industrial countries. The fourth theme discusses efficiency, macroeconomics, conflicts, and dilemmas of fiscal federalism and decentralization, and presents a roundtable discussion on second-generation issues in transition economies
Introduction / Michael Bruno and Boris Pleskovic -- Keynote address: the how of development / Gautam S. Kaji -- Revisiting redistribution with growth: Inequality, poverty, and growth: where do we stand? / Albert Fishlow -- Research on poverty and development twenty years after redistribution with growth /Pranab Bardhan -- Demographic change and development: Government provision and regulation of economic support in old age / Peter Diamond -- Engendering economics: new perspective on women, work, and demographic change / Nancy Flobre -- Aid and development: why is there multilateral lending? / Dani Rodrik -- Incentives, rules of the game, and development / Elinor Ostrom -- Is growth in developing countries beneficial to industrial countries? / Richard N. Cooper -- Fiscal decentralization: Fiscal federalism and decentralization: a review of some efficiency and macroeconomic aspects / Vito Tanzi -- Conflicts and dilemmas of decentralization / Rudolf Hommes -- Roundtable discussion: second generation issues in transition
Includes bibligraphies
Keywords: Economic development; ECONOMIC DEVELOPMENT; INCOME DISTRIBUTION; FINANCIAL AID; Demographic change; DEVELOPING COUNTRIES; CONFERENCES